2014
DOI: 10.1111/2041-210x.12177
|View full text |Cite
|
Sign up to set email alerts
|

Arboreal camera trapping: taking a proven method to new heights

Abstract: Summary1. Although camera trapping has been shown to be a highly effective non-invasive tool for wildlife monitoring, the technique has not yet been widely applied to studies of arboreal species. Despite the unique challenges that camera trapping in the canopy poses, its versatility and relatively non-invasive nature, combined with recent technological improvements on the cameras themselves, make camera trapping a highly useful tool for arboreal research.2. We present data on the methodology and effectiveness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
111
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(119 citation statements)
references
References 7 publications
4
111
0
4
Order By: Relevance
“…Understanding the effects of anthropogenic disturbance to canopy environments is particularly important given that a number of different taxonomic assessments have suggested that biodiversity within canopy strata is under greatest threat due to habitat modification [4,[7][8][9][10][11]59]. Here we suggest that the arboreal camera trapping method can be both useful and cost-effective in the long term for conservation assessments and can provide opportunities to learn more about some of the most charismatic [12] and threatened species in the world [38,39,54] which may otherwise remain largely unknown and could quietly disappear from our planet. …”
Section: Implications For Conservationmentioning
confidence: 99%
“…Understanding the effects of anthropogenic disturbance to canopy environments is particularly important given that a number of different taxonomic assessments have suggested that biodiversity within canopy strata is under greatest threat due to habitat modification [4,[7][8][9][10][11]59]. Here we suggest that the arboreal camera trapping method can be both useful and cost-effective in the long term for conservation assessments and can provide opportunities to learn more about some of the most charismatic [12] and threatened species in the world [38,39,54] which may otherwise remain largely unknown and could quietly disappear from our planet. …”
Section: Implications For Conservationmentioning
confidence: 99%
“…Camera trapping also provides additional data beyond population abundance or density that can allow researchers to develop a more well-rounded understanding of elusive and difficult-to-study populations. This includes information about population structure, demography, activity and ranging patterns, social interactions, and body condition (Head et al, 2012;Nakashima et al, 2013;Galvis et al, 2014;Gregory et al, 2014). For example, once encounter history data is obtained using camera trapping, more general SCR models for open populations or accommodating non-IDed detections can be developed, allowing researchers to obtain a more detailed understanding of population demographics.…”
Section: Implications For Orangutan Survey Methodsmentioning
confidence: 99%
“…Setting cameras in the trees is one possibility. Recent studies demonstrate that it is possible to obtain captures of primates with arboreal camera traps (Gregory et al, 2014) and cameras placed in carefully selected arboreal locations could supplement records on the ground. This might be especially useful in areas where there is a sex difference in use of the ground, as may be the case at certain locations in Wehea (e.g., sepans) and has been found at other orangutan study sites (e.g., Manduell et al, 2011).…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…Without sufficient observations, it is difficult to make conservation decisions regarding animal presence, population size or habitat preferences. As an alternative to direct observation, many researchers are adopting passive monitoring systems using image capture (Anderson et al., ; Gregory, Carrasco Rueda, Deichmann, Kolowski, & Alonso, ; Schmid, Reis‐Filho, Harvey, & Giarrizzo, ). While image‐based monitoring reduces the effort and invasiveness of documenting animal presence, it generates a large number of extraneous images without animals (Swanson et al., ).…”
Section: Introductionmentioning
confidence: 99%